Isolation of Hemagglutinin and Neuraminidase Subunits of Hemagglutinating Virus of Japan - Maeno, Koichiro (1970)
When purified hemagglutinating virus of Japan (HVJ) was treated with trypsin, two major surface antigens were released from the virus. The “hemagglutinin” subunits obtained by this method were reactive with homologous hemagglutination-inhibition antibody and could be detected by an antibody-blocking test. They adsorbed to but did not agglutinate red cells and thus appeared to be “monovalent.” The neuraminidase subunits were obtained in fully active form and did not adsorb to red cells. This finding suggests that these two activities of HVJ are associated with different subunits of the virus particle. The hemagglutinin and neuraminidase subunits could be partially separated by zonal rate centrifugation or gel filtration on Sephadex G-200. The molecular weights estimated for these subunits were approximately 124,000 and 114,000, respectively. After treatment with trypsin, virus-associated hemagglutinin and neuraminidase activities were both reduced significantly. The electron micrographs of such trypsinized virus particles showed complete or partial loss of surface projections. These results suggested that the subunits obtained by this method seemed to be those projections liberated from the virus by the action of trypsin.